Minat Wirausaha berdasarkan Bidang Keahlian, Lingkungan Keluarga, dan Efikasi Diri Siswa SMK Swasta Se-Kecamatan Depok Kabupaten Sleman - Sholekha, Ulvatus; Purnami, Agustina Sri (Media Manajemen Pendidikan, 2025)
Abstract: This study aims to: (1) examine the entrepreneurial interest of private vocational high school (SMK) students in Depok District based on their field of expertise, family environment, and self-efficacy simultaneously; (2) determine the influence of the field of expertise on entrepreneurial interest; (3) assess the influence of the family environment on entrepreneurial interest; and (4) identify the influence of self-efficacy on entrepreneurial interest. The research employed a quantitative approach using a survey as the primary data collection method. The sample consisted of 100 students from various private vocational high schools across Depok District, selected randomly. The research instrument was a questionnaire designed to measure students’ entrepreneurial interest, field of expertise, family environment, and self-efficacy. Data analysis was conducted using descriptive statistics and regression analysis, with assumption testing including normality, linearity, and multicollinearity tests. The results revealed that the field of expertise, family environment, and self-efficacy collectively have a significant positive effect on students’ entrepreneurial interest. These three independent variables contribute positively to shaping students' entrepreneurial intentions. The findings highlight the importance of strengthening fields of expertise, providing family support, and enhancing self-efficacy to foster entrepreneurial spirit among private vocational high school students.